2019
DOI: 10.1038/s41567-019-0443-6
|View full text |Cite
|
Sign up to set email alerts
|

Stress management in composite biopolymer networks

Abstract: Living tissues show an extraordinary adaptiveness to strain, which is crucial for their proper biological functioning 1,2 . The physical origin of this mechanical behaviour has been widely investigated using reconstituted networks of collagen fibres, the principal load-bearing component of tissues 3,4,5 . However, collagen fibres in tissues are embedded in a soft hydrated polysaccharide matrix which generates substantial internal stresses whose effect on tissue mechanics is unknown 6,7,8 . Here, by combining m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 38 publications
3
66
0
1
Order By: Relevance
“…This is in contrast to previous works that concentrated on the classification of different mechanical regimes of fibrous networks, according to connectivity, bending rigidity and internal pre-stresses (39,(49)(50)(51)(52)(53). Note that high-connectivity networks can represent fibrous biopolymer gels that are more vigorously cross-linked (54)(55)(56) or combined with synthetic gels (57). We take the advantage of the near-affine deformation in such high-connectivity networks to develop and compare with continuum models, which allows us to gain deeper insights into the associated mechanisms.…”
Section: Discrete Fiber Simulations Of a Contracting Cell In An Isotrmentioning
confidence: 57%
“…This is in contrast to previous works that concentrated on the classification of different mechanical regimes of fibrous networks, according to connectivity, bending rigidity and internal pre-stresses (39,(49)(50)(51)(52)(53). Note that high-connectivity networks can represent fibrous biopolymer gels that are more vigorously cross-linked (54)(55)(56) or combined with synthetic gels (57). We take the advantage of the near-affine deformation in such high-connectivity networks to develop and compare with continuum models, which allows us to gain deeper insights into the associated mechanisms.…”
Section: Discrete Fiber Simulations Of a Contracting Cell In An Isotrmentioning
confidence: 57%
“…S5c). At concentrations lower than 3 mg mL À1 , as we previously reported, 53 the samples were too soft to reliably measure an elastic modulus. We note that the ISFs for 4 mg mL À1 and 1 mg mL À1 hyaluronan networks were homogeneous across different fields of view, whereas the ISFs at 2 mg mL À1 showed substantial heterogeneity (see ESI, † Fig.…”
Section: Effect Of Crosslinking On Particle Diffusivity In Hyaluronanmentioning
confidence: 64%
“…However, in this case previous macroscopic rheology data indicated that the network is not fully percolated. 53 This likely explains why we observe heterogeneous dynamics for the 0.6 mm particles with large differences among ISFs measured in different sample regions (see ESI, † Fig. S4).…”
Section: Effect Of Crosslinking On Particle Diffusivity In Hyaluronanmentioning
confidence: 82%
“…Last, an improved understanding of ECM–ECM (e.g., GAG‐collagen) interactions in health and disease will further our understanding of the ways ECM‐protein interactions influence mechanical properties and how to properly model them in vitro. [ 118 ]…”
Section: Remaining Questions and Emerging Materials To Study Fibrosismentioning
confidence: 99%